Trends 2015: Learning and Teaching in European Universities (European University Association (EUA))
EUA has launched the Trends 2015 report, which presents the universities’ perceptions of the changes that have taken place in European higher education over the past five years, particularly in relation to learning and teaching. Based on survey responses of 451 higher education institutions from 46 countries (48 higher education systems), the report outlines the changing context in which higher education institutions operate. In most EHEA countries, universities are coping with the consequences of the economic crisis, which in some places is paired with negative demographic trends and migration. The report identifies a number of steps taken by universities to respond to this context as well as to other European and international trends.

(untitled) - Sursock, Andrée (2015)